Metal-free cyclization of unsaturated hydrazones for the divergent assembly of pyrazolones and pyrazolines - Liu, Xiaobing; Zhou, Yao; Song, Qiuling (Chemical communications (Cambridge, England), 2019)
An oxidative cyclization of ,-unsaturated hydrazones for the divergent assembly of pyrazolones and pyrazolines under metal-free conditions is presented. This divergent synthetic strategy was achieved by controlling the reaction atmosphere. A number of pyrazolines were obtained via 5- exo -trig cyclization when the reaction was performed under N 2 . Whereas when the reaction was conducted under O 2 , diverse functionalized pyrazolones were achieved via oxidative cleavage of the C&z.dbd;C double bond. An oxidative cyclization of ,-unsaturated hydrazones for the divergent assembly of pyrazolones and pyrazolines under metal-free conditions is presented.